Revision of the type species of some cheilostome bryozoan genera in the collection of the Swedish Museum of Natural History - Martino, Emanuela Di (Zootaxa, 2022)
The zoological dry collection of the Swedish Museum of Natural History in Stockholm includes an important, historical bryozoan section that is rich in species and specimens and also diverse from a geographical point of view. This collection also contains the type specimens of the type species of some cheilostome bryozoan genera introduced by several naturalists and bryozoologists between the mid-1800s and 1900s. With a few exceptions, these have not been revised since the advent of scanning electron microscopy as a standard tool for bryozoan taxonomy. Here, the type specimen(s) of the type species of the following six cheilostome genera are described and illustrated using SEM micrographs for the first time: Cheilopora Levinsen, 1909; Fedorella Silén, 1947; Floridina Jullien, 1882; Lepraliella Levinsen, 1917; Smittipora Jullien, 1882; and Stenopsella Bassler, 1952. The type specimen(s) of the type species of the recently introduced Terwasipora Reverter-Gil & Souto, 2019 and the relatively recently revised Doryporella Norman, 1903 are also illustrated for the first time. This revision has identified some erroneous geographical records for some of the species/genera examined, and has led to the proposed synonymy of Stenopsella with Gigantopora Ridley, 1881. Lectotypes have also been selected. All of the images produced will also be publicly available through the SMNH online catalogue. The digitisation of natural history museum collections, with prioritisation of historical type specimens, is of paramount importance to facilitate access to the fundamental taxonomic units for scientists worldwide.